PENGARUH PENULISAN SKRIPSI TERHADAP SIMTOM DEPRESI DAN SIMTOM KECEMASAN PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA ANGKATAN 2014 - Nst, Muhammad Solih; Purwoningsih, Emni; Gultom, Dapot Parulian; Fujiati, Isti Ilmiati (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
Introduction: Stress is a dynamic condition in which someone is confronted between chance, obstacle and demand about what they want, also the resullt will be interprated randomly and important. The prevalence of stress, depression, and anxiety are high. According to WHO in 2015, there were 4,4% of worldwide population (322 million) had depression and 3,6% worldwide population (264 million) had anxiety. Objective : This experiment will study the effect of writing a scription on symptom of depression and anxiety in Medical Student University Of Muhammadiyyah Sumatera Utara 2014. Method : this experiment is descriptive analytic with cross sectional design. Result : Based on the experiment, the symptom of severe anxiety concluded 6 men and 19 women, moderate anxiety concluded 8 men and 20 women, mild anxiety concluded 8 men and 15 women, sampel without anxiety concluded 3 men and 5 women. The symptom of severe depression concluded 3 men, moderate depression concluded 3 men and 7 women, mild depression concluded 7 women, sampel without depression concluded 19 men and 45 women. Conclusion : there are an effect of writing a scription on symptom of anxiety and depression, also there are many type and distrubition of depression and anxiety symtom.Keywords: Depression, Anxiety, Scription.